Coronary Artery Calsification on Chest CT Scan as Coronary Heart Disease Predictor in Lung Cancer Patients - Luths Maharina; Yusup Subagio Sutanto; Widiastuti Widiastuti; Sulistyani Kusumaningrum; Adam Prabata; Hari Wujoso (Jurnal Respirologi Indonesia, 2021)
Background: Lung cancer is widely known has strong association with cardiovascular diseases, including coronary heart disease. Smoking as the main risk factor for lung cancer and coronary artery disease is strongly hypothesized as reason behind this association. Our study aimed to predict ability of coronary artery calcification based on chest CT in prevalence of coronary heart disease in patients with lung cancer. Method: This study had cross-sectional design with consecutive sampling method. Subjects in this study were adults (>18 years old) with lung cancer based on histopathological examination. Result: Forty subjects with lung cancer who undergone chest CT was selected as samples in this study. After calculated with other factors, patients with lung cancer who also had coronary artery calcification lesions in Chest CT had 73 times higher risk to develop coronary heart disease (OR=72.63%;95% CI=3.81-1386.21;P=0.004). In addition, lung cancer subjects who are current and ex-smoker had 46 times higher risk to develop coronary heart disease (OR=45.75;95% Cl=1.14-1987.62;P=0.043). Based on those findings, coronary artery calcification has 86.7% sensitivity, 80.0% specificity, 72.2% PPV and 90.9% NPV for predicting coronary heart disease in lung cancer patients. Conclusion: Coronary artery calcification based on chest CT can be utilized as coronary heart disease predictor in lung cancer patients, especially who are current and ex-smoker. Extensive studies, is needed for strengthen this finding in near future.